Wurmkos : Eden. - La Biennale di Venezia, 49. Esposizione Internazionale d'Arte, Venezia, 2001; Berenga, Adriano; Brollo, Boris; Campanella, Pasquale (Sesto S. Giovanni : Cooperativa Lotta contro l'Emarginazione a r.l., 2001)
Wurmkos ; Abate, Susanna ; Baroni, Sara ; Campanella, Pasquale ; Cravera, Alessandro ; De Blasio, Roberto ; De Robertis, Isabella ; Bartolomeo, Angela Di ; Fede, Salvatore ; Lovaglio, Samuele ; Orioni, Raffaella ; Parmiani, Valentina ; Russo, Antonio ; Santoro, Nicola ; Valente, Antonio
Wurmkos : Eden, La Biennale di Venezia, 49. Esposizione Internazionale d'Arte, Venezia, Spazio Berengo, Murano, 9 giugno - 9 sttembre 2001
Engels & Italiaans
boek
Keywords: Wurmkos